An Analysis of Digital Libraries Roles in Public Sector Organizations Utilizing VOSviewer - Natsir, Taufiq; Akib, Haedar; Yandra, Alexsander; Wijaya , Indra Dharma; Haedar, Ahmad Wahidiyat (Program Studi Ilmu Perpustakaan UIN Alauddin, 2024)
Digital libraries serve as centralized repositories, significantly improving information access for employees, stakeholders, and the public. This study examines the pivotal role of digital libraries within public sector organizations, focusing on key elements such as information accessibility, efficient resource management, enhanced collaboration and knowledge sharing, and data security and integrity. The data was gathered from the Scopus database, which was then analyzed and visualized using VOSviewer. The study reveals that they enhance resource management efficiency by systematically organizing digital assets and reducing reliance on physical storage. Additionally, these digital hubs foster a collaborative work environment by facilitating seamless knowledge exchange among employees. Moreover, robust security measures are implemented to ensure the integrity of government data, safeguarding against unauthorized access and data breaches. The significance of this study lies in its potential to inform public sector policymakers and administrators about the benefits of adopting digital libraries. By highlighting their impact on efficiency, collaboration, and data security, the study provides valuable insights for enhancing operational effectiveness and fostering a more informed and connected public sector workforce.